SOCIO-ECONOMIC CHALLENGES HINDERING WOMEN ENTREPRENEURS’ BUSINESS SUSTAINABILITY IN GAUTENG PROVINCE - Prince Chukwuneme Enwereji; Bayai Innocent; Timothy Olaniyi Aluko Aluko (Research on Enterprise in Modern Economy Theory and Practice)
Background and objective: This study explored the socio-economic challenges women entrepreneurs face in the Gauteng province of South Africa. It further examines the specific challenges these women encounter in running their businesses.